THE EFFECT OF FINANCIAL MANAGEMENT BEHAVIOR, SELF-EFFICACY AND HERDING BEHAVIOR ON INVESTMENT DECISIONS MEDIATED BY E-TRUST - Nanda Ainur Khorimah; Dina Yeni Martia; Amanda Eka Aprilia; Cahaya Nur Jamilah; Excel Surya Pamungkas (Jurnal Ilmiah Ekonomi Bisnis, 2025)
The phenomenon shows that Generation Z tends to choose fast and efficient digital services, including investment applications, as their trust in technology fosters a sense of comfort and security in transactions. This study aims to evaluate the effects of financial management behavior, self-efficacy, and herding behavior on investment decisions, with e-trust as a mediating variable. A quantitative approach was applied using structural equation modeling (SEM-PLS) with a sample of 114 active students from Politeknik Negeri Semarang who had invested in stocks. The research instrument employed a 4-point Likert scale to measure the five variables. The results indicate that e-trust has a significant effect on investment decisions, and herding behavior significantly influences e-trust. Conversely, financial management behavior and self-efficacy show no significant direct or indirect effects on either e-trust or investment decisions. The mediation analysis confirms that e-trust only mediates the relationship between herding behavior and investment decisions, but not the other variables. The R² values for e-trust (91.6%) and investment decisions (93.7%) suggest relatively high predictive power, though potential overfitting should be considered. The findings highlight the importance of building digital trust and acknowledging social influence in financial education strategies and the development of investment platforms, particularly for gen Z.